2019
DOI: 10.1007/s40264-019-00893-4
|View full text |Cite
|
Sign up to set email alerts
|

Brand-Specific Enhanced Safety Surveillance of GSK’s Quadrivalent Seasonal Influenza Vaccine in Belgium, Germany and Spain for the 2018/2019 Season

Abstract: Introduction Seasonal influenza causes numerous deaths worldwide each year. Annual vaccination for disease prevention is crucial. Seasonal vaccines are updated each year to closely match circulating strains. Objective To comply with European Medicines Agency (EMA) guidance, an enhanced safety study was conducted to rapidly collect and assess adverse events (AEs) within 7 days following vaccination with GSK's inactivated quadrivalent seasonal influenza vaccine (IIV4) in 2018/2019. Methods A customised AE report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
1
14
1
1
Order By: Relevance
“…A similar pattern has also been seen for Guillain–Barre syndrome, wherein VAERS database analysis has shown possible association [ 9 ], but not a recent nested case–control study [ 12 ]. Also, the data from the surveillance studies differ from our study data [ 19 22 ]. While about 5% of the facial paralysis events were associated with Guillain–Barre syndrome in our study, no cases of Guillain–Barre syndrome were reported in the surveillance studies.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…A similar pattern has also been seen for Guillain–Barre syndrome, wherein VAERS database analysis has shown possible association [ 9 ], but not a recent nested case–control study [ 12 ]. Also, the data from the surveillance studies differ from our study data [ 19 22 ]. While about 5% of the facial paralysis events were associated with Guillain–Barre syndrome in our study, no cases of Guillain–Barre syndrome were reported in the surveillance studies.…”
Section: Discussioncontrasting
confidence: 78%
“…While about 5% of the facial paralysis events were associated with Guillain-Barre syndrome in our study, no cases of Guillain-Barre syndrome were reported in the surveillance studies. Most of these studies were conducted in the United Kingdom, but a recent surveillance study of 1060 vaccinated individuals from Belgium, Germany and Spain also showed similar findings [22]. Hence, if an association between facial paralysis and influenza vaccine does actually exist, the risk is likely to be very low.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, we did not find any signal about differences in AEIs from the enhanced surveillance we conducted for GSK in that year. The practices who took part were excluded from this analysis as we felt they might have increased their AEI awareness and recording [37]. It is possible that the EMA goals might be better achieved through systematic data collection across sentinel networks.…”
Section: Key Resultsmentioning
confidence: 99%